#BringBackOurGirls: digital communities supporting real-world change and influencing mainstream media agendas. Issue 5 (2nd September 2016) - Carter Olson, Candi
Abstract: #BringBackOurGirls shows the potential that cyber-communities have for setting the agenda for mainstream media sources around issues that are life-changing for women and girls around the world. The article examines the ways that social media communities sustained the hashtag #BringBackOurGirls, bridging online and offline communities to form a united movement. The analysis is contextualized within the online community-organizing framework of Twitter Topic Networks, as theorized in a 2014 study by the Pew Research Center Internet and American Life Project. This essay studies the evolution of #BringBackOurGirls to analyze the ways that online communities can educate, organize, and mobilize publics.